OLEMACH THEOREM: ANGULAR-MOMENTUM CONSERVATION IMPLIES GRAVITATIONAL-REDSHIFT PROPORTIONAL CHANGE OF LENGTH, MASS AND CHARGE - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
There is a minor revolution going on in general relativity: a â€œreturn to the mothersâ€œ â€“ that is, to the equivalence principle of Einstein. Recently, the Telemach theorem was described. Here now, the completely independent but fully convergent â€œOlemach theoremâ€ is introduced. It connects omega (rotation rate), length, mass and charge in a static field. The predictable consequence of the two theorems is a return to the hard core of general relativity at the expense of some peripheral features. A connection to cosmology is mentioned along with a promising technological development.